Study on different behaviour of poly(vinylidene fluoride)-polyhedral oligomeric silsesquioxane nanocomposites in mechanical properties and nano-tensile testing. (18th September 2016) - Liu, Y.; Sun, Y.; Yu, J.; Zeng, F.; Xiao, Y.; Geng, L.; Lv, P.
Abstract : Nanocomposites consisting of a poly(vinylidene fluoride) (PVDF) matrix and 0, 3, 5 and 8 wt-% fluoropropyl polyhedral oligomeric silsesquioxane (FP-POSS) were prepared using the solvent evaporation method. The mechanical properties of nanocomposites were investigated by universal mechanical testing and nano-tensile testing. The results derived from two different scales testing both indicated that a small addition of FP-POSS exhibited a positive reinforcement effect of mechanical properties. Meanwhile the reason of the different variation trend of mechanical properties derived from testing standards under different scales was analysed, and the specific role and multi-performance of POSS were estimated.